The Effect of Mycobacterium avium Complex Infections on Routine Mycobacterium bovis Diagnostic Tests. (13th June 2011) - Barry, Claire; Corbett, David; Bakker, Douwe; Andersen, Peter; McNair, Jim; Strain, Sam
Abstract : Bovine tuberculosis (bTB) is diagnosed in naturally infected populations exposed to a wide variety of other pathogens. This study describes the cell-mediated immune responses of cattle exposed to Mycobacterium avium subspecies paratuberculosis (Map) and Mycobacterium avium subspecies avium with particular reference to routine antefmortem Mycobacterium bovis diagnostic tests. The IFN-γ released in response to stimulated blood was found to peak later in the Map-exposed group and was more sustained when compared to the Maa-exposed group. There was a very close correlation between the responses to the purified protein derivatives (PPD) used for stimulation (PPDa, PPDb, and PPDj) with PPDa and PPDj most closely correlated. On occasion, in the Map-infected cattle, PPDb-biased responses were seen compared to PPDa suggesting that some Map-infected cattle could be misclassified as M. bovis infected using this test with these reagents. This bias was not seen when PPDj was used. SICCT results were consistent with the respective infections and all calves would have been classed skin test negative.